Comparing Normal and Multiple Sclerotic Patients Short Term Memory - Mahboubeh Parsaeian; Abdolrahman Najl-Rahim; Masoud Karimlou; Mohammad Mozaffari (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: Multiple sclerosis (MS) is a disease of the central nervous system. The main pattern of neuropsychological impairment in M.S. patients characterized with deficits of attention and memory. Memory problem are known to occur in approximately 50% to 60% of people with M.S. The purpose of the present study is to asses memory function in M.S. patients. Materials & Methods: 40 M.S. patients (30 patients suffering from as relapsing - remitting and 10 patients are chronic progressive M.S.) assessed using Luria - Nebraska memory scale. Results: All of multiple sclerosis patients (without sever depresive state evaluated by BDI) exhibited significant impairments in all of memory veriable (verbal , non - verbal , delayed and whole memory performance) as compared with control groups (normal subjects). Difference of memory performance between the patients with two type of M.S. were not significant. Furthermore no significant relation was found between memory loss and MRI lesions.  Conclusion: This study is guidedas such one can lead to a better understanding of memory deficits in M.S. patients. In addition, specific rehabilitation strategies can be planed on the patterns of memory impairment in M.S. patients.